Enhanced sensing ability in multiple Fano resonance optical biosensor with high-contrast metastructures - Liping Bi; Xinye Fan; Hening Zhao; Lantao Liu; Xin Wei; Huijuan Niu; Chuanchuan Li; Chenglin Bai; Wenjing Fang (Results in Optics, 2022)
Multiple Fano resonance optical sensors based on high-contrast metastructures (HCM) are designed in this paper, combining the temporal coupled-mode theory (TCMT) with the eigenmode information to investigate the resonance mechanism and optical sensing characteristics. The results demonstrate that three sharp Fano peaks with the modulation depths can reach nearly 100 %, which is caused by the interference between the guided mode resonance and the eigenmode. The resonance peaks linewidth of the transmission spectra decreases upon increasing the distance between the grating strips. The maximal Q-factor can exceed 104, the sensitivity (S) is 642.5 nm/RIU and the figure of merit (FOM) is 1717.9.